ACCOUNTING OF CONSTANT LOADS’ VARIABILITY IN CALCULATION OF BUILDINGS’ AND STRUCTURES’ CONSTRUCTIONS - Y. V. Krasnoshchekov (Вестник СибАДИ)
Introduction. The article presents the investigation results of the factors determining the reliability coefficients’ values of the constant load from the weight of the structures in the buildings’ and bridges’ calculation by the method of limiting states. Materials and methods. However, the constant load has not yet been determined due to the lack of the experimental data, the variability influence of each individual factor: the density of the material and structural dimensions on the reliability coefficients’ value. The reliability coefficients’ values of the constant load from the weight of the structures are also determined mainly by the specified reliability and the allowed variability in the structure dimensions. Results. The probabilistic approach’s application to the reliability coefficients’ estimation on the load allows reasonably assign and reduce the calculated values of the constant loads. The application of the probabilistic method of the dispersions’ summation therefore leads to the reduction of the reliability factor for the loads of the self-weight and multi-layer bridge structures to 10%. Discussion and conclusion. The self weight’s variation coefficient of the multilayer structures depends on the control during their manufacture and operation, so the reliability factor for the self weight loads of the multilayer structures could be significantly reduced by the established control. In order to improve the bridges’ reliability and because of the large variability in the pavement elements’ weight, especially in the asphalt-concrete layers’ weight, their normative values should be assigned with the increased security